DEVELOPING CHILDREN'S IMAGINATION THROUGH THE STORY METHOD - Miftahul Jannah; Ahmad Fajian; Husin; Rizka Maulida; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Nowadays there are many visual media or other media that influence children's imagination. Which causes a decrease in children's imagination. The child's imagination begins to decline, this is due to the existence of visual media that makes it easier for someone to tell a story through several pictures, or to show the events of a story directly. This study aims to develop children's imagination of stories read, heard, or stories told by someone, and direct them in a positive direction, not in a negative direction. The research method used is the library research method or library research. The results obtained from this study are that a child's imagination can be developed using the story method with a variety of structured stories, using language that is easy to understand, attractive illustrations and designed in such a way. And there are several things that need attention in the story so that it is in a positive direction and not in a negative direction. In developing a child's imagination, it is necessary to pay attention to several things related to the child's imagination, such as the characteristics of the child and some stories that do not contain elements of a sad story.